Pengaruh Partisipan Anggaran dan Akuntansi Pertanggung Jawaban terhadap Kinerja Manajerial PDAM Kota Padang - Elsa Meirina; Gusairo Rigilang Aziora (JURNAL PUNDI, 2020)
ABSTRACTThis study aims to determine the effect of budget participants and accountability accounting used in the PDAM Kota Padang in order to improve managerial performance. Classified as quantitative research. The population used in this study are all employees working in PDAM Padang City, so the sample of this study is employees who occupy lower level managerial positions. This is because the policy of the company only allows lower-level managers (assistant managers) who are allowed to answer respondents. A total of 36 respondents, and the sampling technique is using proprietary sampling techniques and using a simple linear regression test with independent variables budget participants and accountability accounting as well as managerial performance dependent variables in PDAM Padang City. The results of this study from 36 respondents after testing it can be concluded that budgetary and accounting participant accountability for managerial performance has a significant positive effect.Keywords : Budget Participants, Responsible Accounting and Managerial  Performance.